Annie (2014) [videorecording (DVD)] - Gluck, Will; Wallis, Quvenzhané, 2003-; Foxx, Jamie; Diaz, Cameron; Strouse, Charles; Meehan, Thomas; Charnin, Martin; Gray, Harold, 1894-1968 (Sony Pictures Home Entertainment, 2015)
A contemporary adaptation of the 1977 Broadway musical of the same name, Annie is a young, happy foster kid who's also tough enough to make her way on the streets of New York. Originally left by her parents as a baby with the promise that they'd be back for her someday, it's been a hard knock life ever since with her mean foster mom Miss Hannigan. But everything's about to change when the hard-nosed tycoon and New York mayoral candidate Will Stacks, advised by his brilliant VP, Grace and Guy, makes a thinly-veiled campaign move and takes her in.